Different heat treatments in rice processing affect the nutritional and microbiological aspects of rice bran incorporated poultry feed - Senadeera, K.I.S.; Karunanayake, K.P.V.R.; Yapa, P.N. (University of Jaffna, 2022)
Rice bran, a byproduct of the rice milling industry, is used for poultry feeding in Sri Lanka. High fiber content, rancidity development, enzyme inhibitors, and high mold growth, limit its potential to use as a poultry feed ingredient. The present study was carried out to evaluate the effect of different heat treatments; parboiling, autoclaving, microwave heating, and dry heating on the nutritional value and microbiological safety of rice bran incorporated poultry feed. Two rice varieties, BG 358 and Gonabaru were used. Control and four treatments as crude (T1), parboiled (T2), autoclaved (T3), dry heated (T4), and microwave heated (T5) rice bran of each rice variety was incorporated into the formulated poultry feed. Changes in nutritional value with different treatments were compared by analyzing crude protein, total lipid, and crude fiber contents. Moisture content, and total fungal and bacterial counts were measured during the four- week storage. Data were analyzed in a completely randomized design using MINITAB software. Crude protein, crude fiber, and moisture content were significantly reduced (p<0.05) in heat-treated rice bran incorporated poultry feed of two tested rice varieties, compared to non-heated control. Significantly high lipid content (p<0.05) and lowest fungal and bacterial counts were shown in T5 and independent of the tested rice variety. Although the values are different, the effect of the heat treatments on the nutritional quality and microbiological safety of rice bran incorporated poultry feed is affected in the same manner for two tested rice varieties.
Keywords: Heat treatment; Nutritional value; Poultry feed; Rice bran